Formy spędzania czasu wolnego w okresie pandemii z wykorzystaniem internetu - Kolny, Beata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The Internet, almost from the moment of popularization and wide availability, began to play an important role as one of the possibilities of spending leisure time. It played a special role during the lockdown, enabling contact with other people, participation in culture and the development of physical and intellectual activity. The aim of the article is to present the forms of spending leisure time during the COVID-19 pandemic using the Internet, mobile applications and smart devices. It was written on the basis of secondary and primary sources of information. Direct research was conducted in 2021 on a sample of 620 adult Poles using the online survey technique. Research shows that during a pandemic, consumers are very eager to use the possibilities offered by the Internet to watch movies and series via Internet TV, listen to music via streaming services, contact their friends via instant messaging, and use social media. In addition, they use mobile applications to monitor physical activity and during tourist trips, as well as learn online for fun.
Keywords: leisure; Internet; mobile applications